The New Political Economy of Pharmaceuticals
XVI, 265 p. 12 illus.
Keywords: Some two decades will shortly have passed since the WTO's Trade Related Aspects of Intellectual Property Rights agreement came into force in 1995. This volume is the first cross-country analysis of how TRIPS has affected the capacity of 11 major low or medium income countries to produce generic drugs.